2018
DOI: 10.1155/2018/3870583
|View full text |Cite
|
Sign up to set email alerts
|

Point Load Test of Half‐Cylinder Core Using the Numerical Model and Laboratory Tests: Size Suggestion and Correlation with Cylinder Core

Abstract: The point load test (PLT) is intended as an index test for rock strength classification or estimations of other strength parameters because it is economical and simple to conduct in the laboratory and in field tests. In the literature, calculation procedures for cylinder cores, blocks, or irregular lumps can be found, but no study has researched such procedures for half-cylinder cores. This paper presents the numerical model and laboratory tests for half-cylinder and cylinder specimens. The results for half-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Second, the flat-joint model is selected in the bonded-particle model. Because it can be applied to hard rock, and larger ratio of uniaxial compression strength to tensile strength can be obtained [33]. As shown in Figure 2, the flat-joint contact simulates the behavior of an interface between two notional surfaces (called faces), each of which is rigidly connected to a piece of a body [32].…”
Section: Synthetic Rock Mass (Srm)mentioning
confidence: 99%
“…Second, the flat-joint model is selected in the bonded-particle model. Because it can be applied to hard rock, and larger ratio of uniaxial compression strength to tensile strength can be obtained [33]. As shown in Figure 2, the flat-joint contact simulates the behavior of an interface between two notional surfaces (called faces), each of which is rigidly connected to a piece of a body [32].…”
Section: Synthetic Rock Mass (Srm)mentioning
confidence: 99%
“…In the approaches of cavability assessment, the indices of the rock strength were the uniaxial compressive strength (UCS) or point load strength index (Is (50) ). Determining the Is (50) was a more practical, time-saving, and economical method compared to determining the UCS [30]. A large number of studies [31][32][33][34] have shown that the Is (50) has a good correlation with the UCS.…”
Section: Determination Of the Influencing Factors And Assessmentmentioning
confidence: 99%
“…Also, there are many studies in the literature that were researched the relationships between PLI and other rock properties. Ren et al [32] established a correlation of failure load between half-core and core samples with a fit size suggestion and size correction factor. Mesutoğlu and Özkan [33] made a study to determine the material characteristics of coal and inner burdens using relationships between the Schmidt hardness and PLI values.…”
Section: Introductionmentioning
confidence: 99%